1996
DOI: 10.1016/s0006-3495(96)79528-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA melting investigated by differential scanning calorimetry and Raman spectroscopy

Abstract: Thermal denaturation of the B form of double-stranded DNA has been probed by differential scanning calorimetry (DSC) and Raman spectroscopy of 160 base pair (bp) fragments of calf thymus DNA. The DSC results indicate a median melting temperature Tm = 75.5 degrees C with calorimetric enthalpy change delta Hcal = 6.7 kcal/mol (bp), van't Hoff enthalpy change delta HVH = 50.4 kcal/mol (cooperative unit), and calorimetric entropy change delta Scal = 19.3 cal/deg.mol (bp), at the experimental conditions of 55 mg DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
212
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(231 citation statements)
references
References 29 publications
18
212
0
1
Order By: Relevance
“…We have previously shown that short DNA duplexes of 21 base pairs (dsDNA 21 ) mediate AgSp nanoparticle aggregation acting as electrostatic molecular linkers.…”
Section: Direct Sers Analysis Of Dna: What Do We See?mentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that short DNA duplexes of 21 base pairs (dsDNA 21 ) mediate AgSp nanoparticle aggregation acting as electrostatic molecular linkers.…”
Section: Direct Sers Analysis Of Dna: What Do We See?mentioning
confidence: 99%
“…[16] As a result, dsDNA 21 behaves as a rigid rod of ≈7 nm length and 2 nm diameter, which is collected at the surface of individual quasispherical nanoparticles of around 22 nm diameter with minimal bending of the double helix. [10] Molecular dynamics simulations of dsDNA 21 adsorption on AgSp nanoparticles previously indicated that the duplex rapidly adheres onto the metal surface adopting an elongated conformation (for low surface coverage).…”
Section: Direct Sers Analysis Of Dna: What Do We See?mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is possible to monitor the denaturing processes (transition from ordered double stranded to a disordered single-stranded helix) and the B→A and B→Z conformational changes (Duguid et al, 1996;Erfurth & Peticolas, 1975;Prescott et al, 1984;Taillandier et al, 1989). Collected in Table 5 are the main Raman lines observed during the melting process and the B→A (Z) transitions.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Collected in Table 5 are the main Raman lines observed during the melting process and the B→A (Z) transitions. This technique also enables examination of the structural changes of DNA caused by radiation (Synytsya et al, 2007), temperature and pH change (Duguid et al, 1996;Erfurth & Peticolas, 1975;O'Connor et al, 1982) and the addition of metal ions or organic compounds (Duguid et al, 1993;Langlais et al, 1990;Martin et al, 1978;Martin et al, 1982). The Raman spectrum can be divided into characteristic spectral regions.…”
Section: Raman Spectroscopymentioning
confidence: 99%